2019
DOI: 10.1016/j.sjbs.2017.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of mycorrhizal fungi on seed germination and growth in terrestrial and epiphytic orchids

Abstract: Epiphytes constitute over 70% of orchid diversity, but little is known about the functioning of their mycorrhizal associations. Terrestrial orchid seeds germinate symbiotically in soil and leaf litter, whereas epiphytic orchids may be exposed to relatively high light levels from an early stage of development and often produce green seeds. This suggests that seedlings of the two groups of orchids may differ in their responses to light and requirements for mycorrhiza-supplied carbon. The interactive effects of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 30 publications
1
18
0
1
Order By: Relevance
“…The improvement under stress conditions was markedly higher than that under non-stress conditions (P ≤ 0.05, Tables 4 and 5). Similar improvements in seed germination and seedling growth induced by mycorrhizal fungi inoculation with seeds have also been reported on Dendrobium officinale (Tan et al 2014) and other epiphytic orchid species (Alghamdi 2019). The results also showed that X. badius inoculation led to earlier seed germination and greater survival of seedlings compared with the non-inoculated seeds under non-stress and stress conditions.…”
Section: Effect Of Seed Priming With X Badius Suspensions On Seed Gesupporting
confidence: 80%
“…The improvement under stress conditions was markedly higher than that under non-stress conditions (P ≤ 0.05, Tables 4 and 5). Similar improvements in seed germination and seedling growth induced by mycorrhizal fungi inoculation with seeds have also been reported on Dendrobium officinale (Tan et al 2014) and other epiphytic orchid species (Alghamdi 2019). The results also showed that X. badius inoculation led to earlier seed germination and greater survival of seedlings compared with the non-inoculated seeds under non-stress and stress conditions.…”
Section: Effect Of Seed Priming With X Badius Suspensions On Seed Gesupporting
confidence: 80%
“…In recent years, fungal inoculation implemented through seed sowing has been widely confirmed beneficial to crop seed germination and seedling growth (Vujanovic and Germida 2017). For example, promotion effects on seed germination induced by PGPF inoculation with seeds have been reported on barley (Murphy et al 2017), soybean (Waqas et al 2012), rice (Doni et al 2014), maize (Nayaka et al 2010), orchid (Alghamdi 2019), and ect. During seed germination, the symbiotically associated fungi degrade cuticle cellulose resulting in alleviated retardation effect, provide available carbon and produce phytohormones (especially gibberellins and indole acetic acid) (Hock 2012; Hossain et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Factors, such as rainfall and humus type, predict and affect the presence and richness of OMF-associated epiphytic orchids (Izuddin et al, 2019). Interestingly, although epiphytic orchids and terrestrial orchids exhibit different responses to light at the early growth, OMF have parallel ecological importance in overcoming the photoinhibition during germination and early growth (Alghamdi, 2017).…”
Section: Difference and Adaptability Of Omf In Different Habitatsmentioning
confidence: 99%